Analisis Kepuasan Kerja Karyawan PT Bank Mandiri Taspen Kc Jakarta Ditinjau Dari Lingkungan Kerja, Komitmen Kerja Dan Kompensasi: (Studi Di PT Bank Mandiri Taspen Kc Jakarta) - Youhana Tiatira Br Surbakti; MM Tri Susetyaning Mildawani (Universitas 17 Agustus 1945, 2023)
For organizations, the most important asset is human resources, because basically human resources are the driving factor in every activity within the company. For an organization to carry out its activities to achieve its desired goals, it requires good management, especially human resources, because human resources are the main capital for planning, organizing, coaching and mobilizing other resources in the organization. Human resource management is a part of organizational management that focuses on the elements of human resources. The level of job satisfaction is the company's focus in retaining its employees. One of them is PT Bank Mandiri Taspen which is a private company that provides banking services for retirees. PT Bank Mandiri Taspen is a subsidiary of PT Bank Mandiri and PT Taspen which was founded on November 3 1992. Currently the company is trying to improve employee performance by paying attention to employee job satisfaction.The aim of this research is to analyze the impact of employee job satisfaction in terms of the work environment, work commitment and compensation on employees of PT Bank Mandiri Taspen KC Jakarta. The type of research used is descriptive and the method used is quantitative research methods. with the population being all employees of PT Bank Mandiri Taspen KC Jakarta. The sample used in this research was 75 respondents. The research data used is primary data, which was obtained through distributing questionnaires to samples or research respondents. The data analysis techniques used are multiple linear analysis, correlation, coefficient of determination, and hypothesis testing. The research results show that the work environment contributes to job satisfaction. Work commitment contributes to job satisfaction. Compensation contributes to job satisfaction. Then the work environment, work commitment and compensation simultaneously contribute to job satisfaction.